Innováció, etika, felelősség az információ korában. Adalékok az innovációetika fogalmi megalapozásához - Gulyás , Tibor; Szendrő , Péter; Szécsi, Gábor (Kultúratudományi Szemle, 2022)
Innovation, ethics, responsibility in the information age Tibor Gulyás – Péter Szendrő – Gábor Szécsi Traditional communities can be regarded as moral entities that transform the individual through group pressure. Communal existence allows the individual to transcend himself and find partnership with humanity, and determinates the individual’s moral decisions and judgements. A community is based on dynamic reciprocity and responsibility, and is a fountainhead of social capital, that is, of a common set of shared moral values, norms and expectations that can be described as social trust that facilitates cooperation for mutual benefit. We argue that since this social and cultural process leads to a new conceptualization of responsibility and innovation in the information age, it is an important task to create a general ethical framework, value and norm system of innovation.